Meningkatkan Keterampilan Menyimak Cerita Fabel melalui Model Paired Storytelling melalui Media Wayang Kartun di Kelas II Mi BPPKI Cisaat dengan Teknik Project Base Learning (PJBL) - Nurkaidah Nurkaidah; Dwi Kartika Susanti (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2024)
Based on the results of observations, the researchers observed that in Grade II MI BPPI Cisaat when the teacher explained in front of the class the students were less enthusiastic and tended to be busy with their own activities so that students became unfocused and unable to concentrate in listening to learning. Therefore, this study aims to improve the skills of listening to fables through the Paired Storytelling model of wayang cartoon media with the Project Base Learning (PjBL) technique in class II MI BPPI Cisaat. The subjects of this study consisted of 12 male students and 14 female students with a total of 26 students. Instruments used in data collection using the method of observation and written tests. The results showed that there was an increase in students' listening skills. This is evidenced by the average class score in the first cycle of 69 with the listening skill mastery criteria of 70.91% (enough category) and the completeness of learning outcomes of 61.5% (incomplete category). In the second cycle, using the Paired Storytelling model through wayang cartoon media using the Project Base Learning (PjBL) technique, the class average was 82. The criteria for mastery of listening skills were 81.73% (good category) with a completeness percentage of 84.6% (complete category). Based on observations of the results of the first and second cycles, it showed that there was a significant increase in students' skills in listening to fables in grade II MI BPPI Cisaat.